The clarification of sugarcane juice and the use of CA-11 yeast produces better quality cachaca - Mutton, Márcia Justino Rossini [UNESP]; Garcia, Graciany [UNESP]; Teixeira, Vitor [UNESP]; Silva, Aline Ferreira [UNESP]; Costa, Gustavo Henrique Gravatim; Ferreira, Osania Emerenciano (GN1 Sistemas e Publicacoes, 2020)
Cachaca is the second most consumed alcoholic beverage in Brazil, obtained by distilling wine from fermented sugarcane must, and has an alcohol content of 38 to 48% (v/v) at 20 C. The quality of the drink is affected by the raw material used, the treatment of the juice, the type of yeast and the distillation process. The aim of this study was to evaluate the performance of two types of yeast (selected and pressed) and the prior physical and chemical treatment of the sugarcane juice on the quality of the cachaca. The experimental design was completely randomised with 9 replications. The primary treatment was represented by the must (obtained from clarified and non-clarified juice) and the secondary treatment by the types of yeast (CA-11 and pressed biological). The microbiological behaviour of the yeast during fermentation was evaluated together with the chemical composition of the wine and cachaca. The use of selected strains and the prior treatment of the juice resulted in better performance of the fermenting yeasts, producing distillates of suitable physical and chemical standards and quality.
Keywords: Fermentation process; Liming; Quality beverage; Saccharomyces cerevisiae; Selected yeast